PREVALENCE OF COMBINED DYSLIPIDEMIA AND VITAMIN D INSUFFICIENCY IN OBESE CHILDREN - Stefanescu Ioana Maria; Preda D.M.; Buiuca D. I.; Zuga L.; Mirica A. (Romanian Journal of Oral Rehabilitation)
Objective: This paper examines the prevalence and type of dyslipidemia in obese children. We also searched if there is any relationship between vitamin D deficiency and dyslipidemia in these children. Methods: This cohort study was conducted during a period from march 2023 to september 2024. The study included 100 obese children aged 4 to 17 years old from Romania. We collected anthropometric data such as age, sex, tanner stages and BMI were collected and triglycerides, total serum cholesterol, low-density lipoprotein lipoprotein cholesterol and serum 25OH- vitamin D were measured. We selected the children with a BMI of ≥95th percentile for age and sex according to the Endocrine Society Guidelines. Results: 42% of participants have met de dyslipidemia criteria. 33% had hypercholesterolemia (elevated LDL-cholesterol and/or elevated total cholesterol), 18% had hypertriglyceridemia and 9% had both. 50% of the boys and 33% of the girls had dyslipidemia. We found a weak negative correlation between dyslipidemia and older age but without statistical significance. 58% had vitamin D insufficiency. A weak positive correlation between vitamin D insufficiency and dyslipidemia, but without statistical significance. Conclusions: This small cohort study revealed a high prevalence of dyslipidemia in obese children and adolescents, the most prevalent lipid profile anomaly being hypercholesterolemia, followed by hypertriglyceridemia. The prevalence of dyslipidemia was higher in boys. 58% of participants had vitamin D insufficiency. As overweight and obese children are at risk for adult onset diseases, screening for dyslipidemia is needed. We state that special emphasis should be placed on the early prevention of childhood obesity and associated dyslipidemia.